Complementarity merger as a driver of change and growth in higher education. Issue 1 (13th February 2017) - Boling, J. Ruben; Mayo, Donna Taylor; Helms, Marilyn M.
Abstract : Purpose: Mergers in higher education seem to be more common as academic institutions work to control costs and avoid program duplications in challenging economic times and adopt the more common cost saving measures often espoused from business mergers. The purpose of this paper is to highlight successes from a complementarity-based merger of two institutions in the University System of Georgia (USG) and present results over time. Design/methodology/approach: A case study methodology was employed to explain why a particular merger resulted in greater growth compared to other system-wide academic mergers. This research focuses on a single merger of two institutions in Georgia, one of seven such mergers in the USG institutions to date, involving Gainesville State College and North Georgia College and State University to become the University of North Georgia. Observations are made and complimented by secondary data to rank growth among the seven USG consolidations. Findings: The case findings highlight the success from the complementarity of these institutions. While the two were unique institutions, the success of the merger was linked to the underlying complementarity issues. Originality/value: Using the strategic issues inherent in mergers from the business literature, the merger of the two institutions is profiled and discussion and recommendations are provided along with areas for future research.